Theophylline Enhances In Vitro Fertilization and Embryo Production in Buffaloes - I. Akter; Md. Hasanur Alam; M. N. Islam; A. K. Modak; A. Khatun; M. Moniruzzaman (Faculty of Animal Science, Bogor Agricultural University, 2023)
This study aimed to investigate the effect of theophylline on in vitro fertilization of buffalo oocytes and embryo development in subsequent in vitro embryo culture. Cumulus-oocyte complexes (COCs) were collected from large antral follicles of slaughtered buffaloes and matured in vitro for 24 hours. In vitro matured oocytes were fertilized in Brackett and Oliphant’s (BO) media supplemented with four different concentrations of theophylline (0 mM, 2.5 mM, 5 mM, or 10 mM). After 18 hours of in vitro fertilization, some of the oocytes or presumptive zygotes were fixed and stained to assess fertilization, while the others were cultured for 7 days to assess their developmental capacity in vitro. The results showed that theophylline enhanced the penetration rate of spermatozoa into buffalo oocytes. Supplementation of BO medium with theophylline also increased the normal fertilization rate. In subsequent embryo culture, theophylline increased the formation of 8-cell embryo, morula, and blastocyst rate in buffalo. The cleavage rate did not differ significantly between groups. The morula and blastocyst formation percentages were higher in the groups treated with 2.5 mM theophylline than in the control groups. In conclusion, theophylline improves in vitro fertilization rate and embryo production in buffaloes.